Career Choices for Education Students After Completing Studies - Guslianto, Guslianto; Batubara, Aisyah Nur; Hasnah, Hasnah (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to analyze education students' career choices after completing their studies. This research uses quantitative methods with a correlation research type. This research was conducted by distributing questionnaires to one hundred respondents. Data were analyzed by Miles and Huberman. The research results found that 35% became teachers, 30% became lecturers, 9% became entrepreneurs, 7% became tailors, 4% became employees, 4% became marketing, 3% became designers, 5% became architects, and 3% others. The results of this research can be used as initial data for future researchers in studying this problem in the context of different issues.